STRATEGI BELAJAR: PENGAMATAN DINAMIKA MOTIVASI SISWA DI SD NEGERI PASESEH 01 TANJUNGBUMI BANGKALAN MADURA MELALUI MANAJEMEN KELAS, MEDIA PEMBELAJARAN, DAN ETIKA GURU - Alfiyani HD, Ajeng; Aliyah, Nelud Darajatul; Darmawan, Didit (Jurnal Bilqolam Pendidikan Islam, 2024)
He purpose of this study is to analyze and determine the influence of digital literacy, utilization of learning media, teacher ethics on learning motivation of students at SD Negeri Paseseh 01 Tanjungbumi Bangkalan Madura. This quantitative study aims to measure the impact of classroom management, utilization of learning media, and teacher ethics on learning motivation. With this approach, the study will utilize statistical data collection methods to identify and analyze how much each variable contributes to the level of learning motivation. All students in Class VI numbered 57 people when the sample was collected. It can be seen that the number of male respondents was 54.4% and female respondents were fewer than male respondents, which was 45.6%. When viewed from the age group of respondents, the majority were in the age group of 12 years and over, which was 61.4%, while those aged 12 years were 38.6%. Based on the calculation results in Table 4.7, the resulting linear regression equation model is Y = 25.760 + 5.383 (X₁) + 2.888 (X₂) + 3.231 (X₃), where Y is the Learning Motivation variable, and X₁, X₂, and X₃ are the Class Management, Learning Media, and Teacher Ethics variables, respectively. The regression coefficient of 5.383 on the Class Management variable indicates that each unit increase in the Class Management score is followed by an increase of 5.383 in the Learning Motivation score. Likewise, the regression coefficient of 2.888 on the Learning Media variable and 3.231 on the Teacher Ethics variable implies a positive contribution to each of the students' Learning Motivation